2023
DOI: 10.1080/22221751.2023.2204151
|View full text |Cite
|
Sign up to set email alerts
|

Mpox multi-antigen mRNA vaccine candidates by a simplified manufacturing strategy afford efficient protection against lethal orthopoxvirus challenge

Abstract: Current unprecedented mpox outbreaks in non-endemic regions represent a global public health concern. Although two live-attenuated vaccinia virus (VACV)-based vaccines have been urgently approved for people at high risk for mpox, a safer and more effective vaccine that can be available for the general public is desperately needed. By utilizing a simplified manufacturing strategy of mixing DNA plasmids before transcription, we developed two multi-antigen mRNA vaccine candidates, which encode four (M1, A29, B6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…For the development of multivalent or combined mRNA vaccines, encapsulating each mRNA encoding separate antigens is a common approach, despite the efficiency of encapsulating all mRNAs simultaneously (36, 4648). This method of individual LNP preparation facilitates the convenient verification of each mRNA vaccine component’s qualification, concentration, and immunogenicity (46).…”
Section: Discussionmentioning
confidence: 99%
“…For the development of multivalent or combined mRNA vaccines, encapsulating each mRNA encoding separate antigens is a common approach, despite the efficiency of encapsulating all mRNAs simultaneously (36, 4648). This method of individual LNP preparation facilitates the convenient verification of each mRNA vaccine component’s qualification, concentration, and immunogenicity (46).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 As for the development of specific vaccines against mpox, several mRNA vaccines have been reported recently, which found that the mRNA vaccines composed of different antigens from mpox virus can induce a broad spectrum of humoral and cellular immune responses against orthopoxvirus. 7,8 Previously, Zhang et al designed five mRNA sequences that encoded five mpox antigens: M1R, E8L, A29L, A35R, and B6R. In addition, four types of polyvalent mpox mRNA vaccines in combination were constructed.…”
Section: Various Mpox Recombinant Subunits Induce Broadly Reactive An...mentioning
confidence: 99%
“…Therefore, it is important to focus on specific and defined targets for the development of Mpox vaccines rather than relying solely on attenuated virus‐based vaccines. Fortunately, several MPXV antigen‐specific mRNA vaccines are being developed, presenting high effectiveness in triggering immune responses and protecting mice from vaccina virus challenge 52–57 . Moreover, based on MPXV specific protective proteins, our team also developed one subunit vaccine and two mRNA vaccine candidates, all of which showed promising results in inducing cellular and humoral immune responses, as well as anti‐vaccinia virus activity in mouse model 58,59 …”
Section: Vaccination Strategies Against Infection Of Mpxvmentioning
confidence: 99%